The Experience of Depression Relapse among Adult Thai Patients with Depressive Disorder: A Qualitative Study - Muijeen, Kasorn; Soonthornchaiya, Rangsiman; Butcher, Howard K. (Current Psychiatry Research and Reviews, 2022)
Background: Depression is an illness with widespread incidence and has shown an annual increase, while depression relapse is also rising continually due to multiple causes. In Thailand, although many studies have been conducted to prevent depression incidence and relapse, there is little known about the meaning of depression relapse in adult Thai patients. An exploration of the direct experiences of adult Thai patients seems a suitable way to gather data for a care system development. Objectives: The purpose of this study is to describe the perceptions of adult Thai patients concerning their experience of depression relapse and its management among adult patients with depressive disorder in the Thai context. Methods: This research is a qualitative study using the directed content analysis approach. In-depth interviews with 20 adult Thai patients with depression that had direct experience with depression relapse were the participants used in this study. The interviews allowed the participants to talk about their experiences with depression relapse and how they managed depressive symptoms; the interviews lasted approximately 60 minutes. Results: Two themes emerged from the study. First, the experience of depression relapse is the feeling pulled away from happiness. Second, managing depression relapse. Conclusion: Depression relapse among adult Thai patients with depressive disorder is an experience causing patients to feel that they are losing their happiness again. Care and management of depression relapse by each patient differ, despite being in the same social contexts. Therefore, depression relapse risk assessment is important in the care of each patient in order to design more effective care.
Keywords: Experience of relapse